Pengetahuan, Persepsi, Sikap, Motivasi dan Perilaku Keselamatan dan Kesehatan Kerja di Klinik: Studi Kasus di Kota Bangun - Evi Paulina Simanjuntak; Ratih Wirapuspita Wirapuspita Wisnuwardani (J-KESMAS: Jurnal Kesehatan Masyarakat, 2024)
BACKGROUND :Occupational health and safety in an important component of health services, unsafe working conditions are one of poor health services. This study aims to assess knowledge, attitudes, motivation, perceptions and behavior of occupational health and safety at the Rissa Medika Clinic in Kota Bangun. METHOD: this study used a cross-sectional study using a structured queationnaire anf distributed from September to November 2024, taking a total sample of 29 employees. Data were analyzed using chi-square tests.RESULTS; The majority of participants were women with the gighest level of education being a bachelor’s gegree.From the statistics test, it was found that there was a relationship between perception and attitude with a p value=0.001, in terms of motivation and perception, a relationship was also found with a p value=0.001 and in the relationship between occupation health and safety behavior and perception, a relationship was found with a p value=0.023.CONCLUSION: The authors recommend conducting training sessions at Rissa Medika Clinic to enchance workplace behavior and promote safety in the work environment